first
\(\displaystyle{X}{X}{X}{X}={\left({X}\right)}^{{4}}\)

thus

\(\displaystyle{5}{X}{X}{X}{X}={5}{\left({X}\right)}^{{4}}\)

second \(\displaystyle{7}{Y}\cdot{7}{Y}\cdot{7}{Y}={\left({7}{Y}\right)}^{{3}}\)

third \(\displaystyle{r}{r}={\left({r}\right)}^{{2}}\)

\(\displaystyle{2}{t}\cdot{2}{t}\cdot{2}{t}={\left({2}{t}\right)}^{{3}}\)

thus

\(\displaystyle{r}{r}\cdot{2}{t}\cdot{2}{t}\cdot{2}{t}={\left({r}\right)}^{{2}}\cdot{\left({2}{t}\right)}^{{3}}\)

answer

\(\displaystyle{5}{\left({X}\right)}^{{4}}.\)

\(\displaystyle{\left({7}{Y}\right)}^{{3}}.\)

\(\displaystyle{\left({r}\right)}^{{2}}\cdot{\left({2}{t}\right)}^{{3}}.\)

thus

\(\displaystyle{5}{X}{X}{X}{X}={5}{\left({X}\right)}^{{4}}\)

second \(\displaystyle{7}{Y}\cdot{7}{Y}\cdot{7}{Y}={\left({7}{Y}\right)}^{{3}}\)

third \(\displaystyle{r}{r}={\left({r}\right)}^{{2}}\)

\(\displaystyle{2}{t}\cdot{2}{t}\cdot{2}{t}={\left({2}{t}\right)}^{{3}}\)

thus

\(\displaystyle{r}{r}\cdot{2}{t}\cdot{2}{t}\cdot{2}{t}={\left({r}\right)}^{{2}}\cdot{\left({2}{t}\right)}^{{3}}\)

answer

\(\displaystyle{5}{\left({X}\right)}^{{4}}.\)

\(\displaystyle{\left({7}{Y}\right)}^{{3}}.\)

\(\displaystyle{\left({r}\right)}^{{2}}\cdot{\left({2}{t}\right)}^{{3}}.\)